45S5 Bioglass analogue reinforced akermanite ceramic favorable for additive manufacturing mechanically strong scaffolds. Issue 124 (1st December 2015) - Wang, Xiaoqing; Zhang, Lei; Ke, Xiurong; Wang, Juncheng; Yang, Guojing; Yang, Xianyan; He, Dongshuang; Shao, Huifeng; He, Yong; Fu, Jianzhong; Xu, Sanzhong; Gou, Zhongru
Abstract : Mechanically strong akermanite-based porous bioceramic scaffolds with appreciable bioactivity and biodegradation were developed via extrusion 3D-printing followed by a low-melt bioactive glass-assisted pressureless sintering process. Abstract : Calcium–magnesium silicate bioceramics have attracted increased interest in the development of porous scaffolds for bone tissue engineering applications, mainly due to their excellent bioactivity and ability to bond to hard tissue. However, the shaping of these bioceramics into complex porous constructs is challenging, and, especially, conventional high temperature pressureless sintering is not always an effective method to improve their mechanical properties without further compromising their biologically relevant performances. Here we developed a low melting-point bioactive glass (BG)-assisted sintering approach to improve the mechanical properties of akermanite ceramics with and without intentionally manufacturing macroporous structures. The experimental results indicated that the 4 wt% B2 O3 -containing 45S5 BG analogue could readily reinforce akermanite ceramics at a 20–40 wt% content, and material extrusion 3D-printing followed by a pressureless sintering process could be employed to fabricate high-strength porous scaffolds with compressive strength (∼36 MPa) ten times higher than those of pure akermanite porous ceramics. Moreover, the composite porous ceramics showed slower biodegradation in Tris buffer in vitro and this did not heavily affect the strength of their porous formulation over a long time period (6 weeks). It is proposed that 3D printing followed by an NCS-B-assisted sintering process represents an effective alternative for developing high strength bioceramic scaffolds potentially for the repair of load-bearing segmental bone defects.